Typification of ornamental plants 3: Impatiens balsamina (Balsaminaceae) - Christenhusz, Maarten J. M.; Jarvis, Charlie (Phytotaxa, 2013)
Impatiens balsamina Linnaeus (1753: 938) Protologue: “Balsamina. 5. IMPATIENS pedunculis unifloris aggregatis, foliis lanceolatis, nectariis flore brevioribus. Hort. ups. 276. Impatiens pedunculis confertis unifloris. Hort. cliff. 428. Balsamina femina. Bauh. pin. 306. Balsamina. Dod. pemt. 671. Habitat in India. [annual]” Original material: Herb. Linnaeus Nos 1053.3, 1053.4 (LINN), Herb. Clifford: 428, Impatiens 2, 2 sheets (BM), Herb. Burser XVII: 81 (UPS), [icon] in Dodoëns (1616: 671). Lectotype (designated here): Anon. s.n. ex Herb. Linnaeus No. 1053.3 (LINN!).